A different look at Lenin's legacy: Trust, risk, fairness and cooperativeness in the two Germanies - Guido Heineck; Bernd Süssmuth (Institute for the Study of Labor (IZA), 2010)
What are the long-term effects of Communism on economically relevant notions such as social trust? To answer this question, we use the reunification of Germany as a natural experiment and study the post-reunification trajectory of convergence with regard to individuals' trust and risk, as well as perceived fairness and cooperativeness. Our hypotheses are derived from a model of German reunification that incorporates individual responses both to incentives and to values inherited from earlier generations as recently suggested in the literature. Using data from the German Socio-Economic Panel, we find that despite twenty years of reunification East Germans are still characterized by a persistent level of social distrust. In comparison to West Germans, they are also less inclined to see others as fair or helpful. Implied trajectories can be interpreted as evidence for the passing of cultural traits across generations and for cooperation being sustained by values rather than by reputation. Moreover, East Germans are found to be more risk loving than West Germans. In contrast to trust and fairness, full convergence in risk attitude is reached in recent years.
Keywords: P51; Z31; 330; social trust; risk attitudes; political regimes; German reunification; Wirtschaftssoziologie; Vertrauen; Risikopräferenz; Gerechtigkeit; Kooperation; Wahrnehmung; Vergleich; Alte Bundesländer; Neue Bundesländer; Deutschland; Kommunismus; Soziale Werte